2008
DOI: 10.1007/s12264-008-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum adrenocorticotropic hormone and cortisol levels during sleep seizures

Abstract: Objective Measuring the serum concentrations of adrenocorticotropic hormone (ACTH) and cortisol in epileptic seizures during sleep to investigate their link to the EEG changes. Methods Pre-surgical evaluation was performed by video-EEG monitoring using 24 channel recording. Thirty six epilepsy patients could be attributed to two groups: 28 patients had spontaneous seizures, and the other 8 patients whose seizures were induced by bemegride. Another 11 persons with confirmed psychogenic non-epileptic seizures (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Tunca et al reported a rise in cortisol levels during PNES events when compared with basal cortisol levels in HC [54]. Zhang and Liu found a typical pattern of pre-ictal fall and postictal rise of cortisol in ES but no such changes in PNES [55]. Other studies by Bakvis et al have demonstrated PNES patients possess basal hypercortisolism positively correlated with both traumatic histories and threat vigilance [56,57].…”
Section: Other Hormonesmentioning
confidence: 94%
“…Tunca et al reported a rise in cortisol levels during PNES events when compared with basal cortisol levels in HC [54]. Zhang and Liu found a typical pattern of pre-ictal fall and postictal rise of cortisol in ES but no such changes in PNES [55]. Other studies by Bakvis et al have demonstrated PNES patients possess basal hypercortisolism positively correlated with both traumatic histories and threat vigilance [56,57].…”
Section: Other Hormonesmentioning
confidence: 94%
“…Epilepsy, which affects approximately 50 million people worldwide (WHO, ), is characterized by recurrent convulsions/seizures, behavioural impairments, pathological neural activity and endocrine dysfunction (Andrea Galimberti et al, ; Zhang and Liu, ; Green et al, ; Engel, ). Epilepsy can be modelled in larval and adult zebrafish (primarily by administration of convulsant drugs and genetic modifications) and evaluated by various behavioural and physiological endpoints (Wong et al, ; Desmond et al, ; Cunliffe, ).…”
Section: Zebrafish Models Of Major Cns Disordersmentioning
confidence: 99%
“…Also, there is a correlation between the elevated cortisol and the changes of the hypocampal structures in patients suffered by psychosis [23,24]. Furthermore, there are coexistence between the concentration of the cortisol and the epileptic seizure onset [25][26][27]. An elevated corticosteroid level has been measured in meningoencephalitis compared to healthy population [28].…”
Section: Discussionmentioning
confidence: 99%